Progressive exercise training improves maximal aerobic capacity in individuals with well-healed burn injuries - Romero, Steven A. (Am J Physiol Regul Integr Comp Physiol, 2019)
Long-term rehabilitative strategies are important for individuals with well-healed burn injuries. Such information is particularly critical because patients are routinely surviving severe burn injuries given medical advances in the acute care setting. The purpose of this study was to test the hypothesis that a 6-mo community-based exercise training program will increase maximal aerobic capacity (V̇o(2max)) in subjects with prior burn injuries, with the extent of that increase influenced by the severity of the burn injury (i.e., percent body surface area burned). Maximal aerobic capacity (indirect calorimetry) and skeletal muscle oxidative enzyme activity (biopsy of the vastus lateralis muscle) were measured pre- and postexercise training in noninjured control subjects (n = 11) and in individuals with well-healed burn injuries (n = 13, moderate body surface area burned; n = 20, high body surface area burned). Exercise training increased V̇o(2max) in all groups (control: 15 ± 5%; moderate body surface area: 11 ± 3%; high body surface area: 11 ± 2%; P < 0.05), though the magnitude of this improvement did not differ between groups (P = 0.7). Exercise training also increased the activity of the skeletal muscle oxidative enzymes citrate synthase (P < 0.05) and cytochrome c oxidase (P < 0.05), an effect that did not differ between groups (P = 0.2). These data suggest that 6 mo of progressive exercise training improves V̇o(2max) in individuals with burn injuries and that the magnitude of body surface area burned does not lessen this adaptive response.